"How Do You Draw Freedom?". (10th April 2015) - Leland, Christine H.; Ociepka, Anne; Wackerly, Amy
Abstract Children and their teacher participated in a project that explored the question of how engaging in transmediation after hearing a story might affect children's meaning construction. In this article we share our work with a teacher and her third graders as they were challenged to move from the traditional activity of drawing a picture about a story to drawing a picture that symbolized the underlying meaning of a story.